The educational practice of preceptors in healthcare residencies: a study on reflective practice - Kátia Regina Barros RIBEIRO; Marta Lenise do PRADO
The purpose of this article was to reflect on the practice of preceptorship as an educational practice in the training and qualifications of professional health information for the public health system. This is a theoretical reflection with support in the literature. The teacher addresses the teaching-learning process and transforms the activities in the work on educational moments. In this area arise questions about what is being preceptor and their role in health education. It is necessary to teach knowledge beyond the content of the discipline, and reflecting about preceptorship as an educational practice in the workplace, the preceptor needs pedagogical preparation. Herewith, being a preceptor means being a teacher? This reflection places us in front of a problem present in our daily exercise, which is the pedagogical training of those who teach for a transformation of practice in health.